(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2025)
White-syntan-vegetable tanned leather is a durable product processed from skin/hides using white-syntan and vegetable tanning agents. Despite the product’s durability, UV light-induced photodegradation is a major challenge, resulting in discolouration and a loss of physical-mechanical properties. As a photostabilizer, collagen peptide has demonstrated a promising impact due to its natural affinity with protein-based materials and antioxidant properties. The current study assesses the effectiveness of a photostabilizer in improving UV resistance and related properties on white-syntan-vegetable tanned leather. After the treatment with collagen peptide, the photostabilizing capacity and properties of the white-syntan-tanned leather were evaluated through Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR-FTIR), Xenotest LM, a tensile strength testing machine, a scanning electron microscope (SEM), and a leather shrinkage temperature tester. In comparison to untreated samples, the collagen peptide-treated leather showed a notable rise in UV resistance and improvement in physical-mechanical properties. SEM images revealed well-loosened, separated, and opened fibre bundles, while FTIR analysis confirmed the interactions between collagen peptide and the white-syntan-vegetable tanned leather. These findings confirmed that collagen peptide improved the lightfastness and other related properties of leather. Generally, this study emphasizes the potential of collagen peptides as an eco-friendly additive for improving leather performance in UV-prone environments.